Pleiotrophin Expression and Actions in Pancreatic β-Cells - Sevillano, Julio; Liang, Aileen; Strutt, Brenda; Hill, Thomas G.; Szlapinski, Sandra; Ramos-Álvarez, Maria Pilar; Hill, David J. (Frontiers in Endocrinology, 2022)
Pleiotrophin (PTN) is a heparin-binding cytokine that is widely expressed during early development and increases in maternal circulation during pregnancy. Aged PTN-deficient mice exhibit insulin resistance, suggesting a role in metabolic control. The objectives of this study were to determine if PTN is expressed in mouse pancreatic beta-cells in young vs. adult animals, and its effects on DNA synthesis, beta-cell gene expression and glucose-stimulated insulin secretion (GSIS). The Ptn gene was expressed in isolated fractions of young mouse beta-cells, especially within immature beta-cells with low glucose transporter 2 expression. Expression was retained in the adult pancreas but did not significantly change during pregnancy. PTN and its receptor, phosphotyrosine phosphatase-β/ζ, were also expressed in the proliferative INS1E beta-cell line. Fluorescence immunohistochemistry showed that PTN peptide was present in islets of Langerhans in adult mice, associated predominantly with beta-cells. The percentage of -cells staining for PTN did not alter during mouse pregnancy, but intense staining was seen during beta-cell regeneration in young mice following depletion of beta-cells with streptozotocin. Incubation of INS1E cells with PTN resulted in an increased DNA synthesis as measured by Ki67 localization and increased expression of Pdx1 and insulin. However, both DNA synthesis and GSIS were not altered by PTN in isolated adult mouse islets. The findings show that Ptn is expressed in mouse beta-cells in young and adult life and could potentially contribute to adaptive increases in beta-cell mass during early life or pregnancy.